Repeated healing of delamination damage in vascular composites by pressurized delivery of reactive agents. (20th October 2017) - Hart, Kevin R.; Lankford, Seth M.; Freund, Isaac A.; Patrick, Jason F.; Krull, Brett. P.; Wetzel, Eric D.; Sottos, Nancy R.; White, Scott R.
Abstract: Recurrent self-healing of fracture damage in fiber-reinforced composites was accomplished by incorporating internal vascular networks for repeated delivery of reactive liquid components to an internal delamination. Double cantilever beam specimens containing embedded microvascular channels were repeatedly fractured and healed by pumping individually sequestered epoxy and amine based healing agents to the fracture plane. The effect of various pumping parameters and component delivery ratios on in situ mixing of the healing agents and the resulting healing efficiency is reported. Confocal Raman spectroscopy was used to quantify the extent of mixing of healing agents within the fracture plane. Using an optimized healing agent delivery scheme, ten cycles of fracture and healing were achieved with, on average, 55% and as high as 95%, recovery of the virgin critical strain energy release rate.